Teachers’ Perceptions of AI Tools for Enhancing Student Motivation and Learning Engagement in Higher Education - Hermanto Hermanto; Mukarramah Mustari; Athiyyah Sepriani (CV. FoundAE, 2025)
This study examined higher education teachers’ perceptions of AI tools for enhancing student motivation and learning engagement in response to growing interest in AI-supported instruction. Using an explanatory sequential mixed methods design, quantitative data were collected from 98 instructors across three universities in Lampung Province, followed by qualitative interviews with 15 purposively selected participants. Survey measures assessed perceived usefulness, ease of use, motivational impact, engagement impact, and ethical concerns. Quantitative results showed strong perceived motivational benefits of AI and moderate engagement effects, with significant correlations between usefulness and motivation (p < .001) and disciplinary differences in engagement perceptions (p = .019). Qualitative thematic analysis revealed that teachers observed increased confidence and task persistence among students using AI tools but noted uneven engagement linked to digital readiness and expressed concerns about privacy, shallow reasoning, and academic integrity. Integrated findings indicated that while AI is viewed as a supportive motivational resource, its pedagogical value depends on ethical safeguards and student competencies. The study contributes insights into how teachers interpret AI’s educational role, highlighting implications for institutional policy, professional development, and future AI-enhanced learning designs.